PENGGUNAAN ALAT PILE DRIVING ANALYZER DALAM MENENTUKAN DAYA DUKUNG TIANG PANCANG - MAMMING, IDHIL (FORUM BANGUNAN, 2012)
The purpose of the Pile Driving Analyzer Testing (PDA) Test is a static test of single pile bearing capacity. PDA test is conducted after 7 days fixing the time, so the soil has time to return to normal. While the drill pile is done after the drill reached the age of 21 days, so that when the head is struck, the pole is not easily broken. The results of the PDA Test by using the "Case Method" are the carrying capacity of a single pile, integrity or wholeness and connection pole and the efficiency of energy transfer punch hammer / tool saplings.